Analisis Determinan Perubahan Laba Bersih Pada Bank Umum Konvensional Di Indonesia Periode 2011–2015 - Liga Febriani; Ana Mufidah; Sumani Sumani (STIE Mandala Jember, 2019)
The financial performance of the bank describes the financial condition of banks in a given period. The financial performance of bank can be categorized by looking at a bank’s net profit change. Net profit change used by user of financial statements to determine whether there is an increase or decrease in profit, so it can be used as a guide for future managerial decisions. The purpose of this study was to: (1) analyze the NPL is a determinant of commercial bank’s net profit change in Indonesia, (2) analyze the IRR is a determinant of commercial bank’s net profit change in Indonesia, (3) analyze the LDR is a determinant of commercial bank’s net profit change in Indonesia, (4) analyze the ROA is a determinant of commercial bank’s net profit change in Indonesia, (5) analyze the NIM is a determinant of commercial bank’s net profit change in Indonesia, (6) analyze the BOPO is a determinant of commercial bank’s net profit change in Indonesia, (7) analyze the CAR is a determinant of commercial bank’s net profit change in Indonesia. Data used in this research is secondary data. The population in this study is the banks listed on the Indonesia Bank in the period 2011–2015. Taking the number of samples by purposive sampling method used multiple linear regression analysis. The test results and data analysis were performed with SPSS 21 showed that: NPL, IRR, ROA, and NIM are determinant of commercial bank’s net profit change in Indonesia; LDR, BOPO, and CAR ratio are not determinant of commercial bank’s net profit change in Indonesia.